The Type of Fish and Storage Time to The Characteristics of Pedetan in Jembrana Bali - Ni Made Ayu Suardani Singapurwa; I Wayan Sudiarta; Anak Agung Made Semariyani; Mariam Lupita Kant (SEAS (Sustainable Environment Agricultural Science), 2017)
Abstract This study aims to determine the study of fish type and storage time to the characteristics of 'pedetan' fish in Jembrana-Bali. This research was conducted in March-May 2015 at Agricultural Processing Laboratory of Agricultural Faculty of Warmadewa University and TVB (Total Volatile Base) analysis was conducted at Fishery product and Quality Control Laboratory of Bali Province. The design used was Factorial Randomized Block Design (RAK) pattern consisting of two treatments and three replications. The first treatment is fish, the type of Sardinella sirm and Sardinella bleeker. The second treatment is the storage time which is consisting of 7 levels ie storage time 0 week, 2 weeks, 4 weeks, 6 weeks, 8 weeks, 10 weeks, and 12 weeks. Observations are made objectively and subjectively. Objective observations include water content, acidity (pH), weight change, and TVB. Subjective observations include appearance, odor, taste, texture, and fungus using assessment method in accordance with the Indonesian standard of quality (SNI 2721.1: 2009). From the objective observation result, water content ranged from 8.13 to 17.07%, pH 6.18-6.55, weight loss 0 - 1.44%, and TVB 34.22 - 53.62 mg-N / 100gram, and subjective observations obtained with specification values ranging from 7.13 to 8.27, odor 7.15 - 8.31, flavors 7.07 - 7.71, texture 7.22 - 7.91, mushrooms (no mushrooms). All analysis parameters above meet the Indonesian standard of quality (SNI 2721.1: 2009). From the results of the study, it was found that Sardinella sirm and Sardinella bleeker with a duration of 12 weeks can maintain the characteristics of pedetan on storage. Keywords: Pedetan, Sardinella sirm, Sardinella bleeker.